Analysis of family economic education in fostering entrepreneurial spirit: A phenomenological study of beneficiary families with businesses - Saleng, Tenri Agus; Dinar, Muhammad; Hasan, Muhammad; Inanna (Journal of Socio-Cultural Sustainability and Resilience, 2025)
Background: This study aims to explore information on how family economic education influences the growth of entrepreneurial spirit among the beneficiaries of the Family Hope Program/Program Keluarga Harapan (PKH) who own businesses in Tellulimpue District, Sidrap Regency. Methods: This research is a quantitative study with a descriptive quantitative approach. The subjects of this research are the PKH beneficiaries who own businesses. Data collection methods were conducted through interviews and observations. Findings: The results show that family economic education has been instilled by PKH beneficiaries who own businesses in Tellulimpue District. They do this by involving their children in business activities to foster discipline. Conclusion: Family economic education is capable of nurturing the entrepreneurial spirit of PKH beneficiaries with businesses in Tellulimpue District because it motivates children to aspire to have their own businesses in the future through an entrepreneurial spirit. Novelty/Originality of this article: The novelty of this research lies in analyzing how family economic education among recipients of the Family Hope Program (PKH) contributes to fostering an entrepreneurial spirit not only for parents, but also for their children.